A 56 Year Old Man with Parkinson’s Disease and Depression: A Case Report on Treatment Management - Risza Subiantoro; Agustina Konginan; Erikavitri Yulianti (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Depression is the strongest predictor of quality of life for Parkinson’s disease (PD).Presentation of Case: A 56 years old man came with the main complaint of difficulty sleeping due tothinking about tremors in his left hand since 6 months. Complaints are accompanied by feelings of sadness,lack of enthusiasm, and decreased appetite accompanied by weight loss. The patient had been diagnosedwith PD 8 years previously and was on medication. One month before the visit, the patient underwent athalamotomy operation. After surgery, the patient received therapy in the form of a combination tabletof levodopa/carbidopa/entacapaone (100/25/200 mg) 4×1 tablet and 1×2 mg of ropirinole. On the BeckDepression Inventory (BDI) examination, a score of 23 was obtained and on the Montgomery AsbergDepression Rating Scale (MADRS) examination a score of 31 was obtained, both of which correspond tomajor depression. The patient was diagnosed with a major depressive episode without psychotic symptomsand was given escitalopram therapy 1×10 mg and lorazepam 1×2 mg. Patients also received biofeedbacktherapy with family psychoeducation and supportive psychotherapy. At the time of control, the patientadmitted to feeling calmer and able to sleep after receiving therapy. Conclusion: Escitalopram has goodefficacy for the management of depression in PD patients.